USING VISUAL ARTS TO ENHANCE ENGLISH POETRY COMPREHENSION FOR ENGLISH LANGUAGE AND LITERATURE STUDENTS (Hiski Malang, 2019)
Poetry as a genre of literature is required subject for students of English Language and Literature in Higher Education in general. However, compared to other genres such as drama and prose, poetry is often found as the most challenging subject to teach and to learn. Even though English poetry has been taught in many non-native countries for many years, traditional approach which is textual has dominated the teaching of poetry in classroom. Based on the experience and knowledge, the writers found that the problem of learning English poetry for foreign language students is due to its complex language and infamous interest amongst the students as well as the teachers. Therefore, the teaching of poetry should enliven the learning atmosphere and envision the figure of speech of the poem, which are commonly found to be difficult to be done by the students. According to D.H. Kehl, there is somehow interconnection between poetry and visual arts. Poetry and visual arts have almost the same characteristic in conveying arts. Poetry use verbal imagery while painting use visual imagery. Considering the existing connection of the two aspects, this library research study proposes the use of visual arts in order to enhance students’ comprehension of poetry given in classroom.